Polysaccharide PCP-I isolated from Poria cocos enhances the immunogenicity and protection of an anthrax protective antigen-based vaccine - Kun Liu; Ying Yin; Jun Zhang; Xiaodong Zai; Ruihua Li; Hao Ma; Junjie Xu; Junjie Shan; Wei Chen (Taylor & Francis Group, 2020)
Polysaccharides isolated from natural plants may represent a novel source of vaccine adjuvants. In this research, we focused on a natural plant polysaccharide, PCP-I, which is derived from Poria cocos, a Chinese traditional herbal medicine. We chose the anthrax protective antigen (PA) as a model to evaluate the adjuvant ability of PCP-I in enhancing the immunogenicity and protection of a PA-based anthrax vaccine. According to our results, PCP-I could significantly enhance anthrax specific anti-PA antibodies, toxin-neutralizing antibodies, anti-PA antibody affinity, as well as IgG1 and IgG2a levels. Besides, PCP-I increased the frequency of PA-specific memory B cells, increased the proliferation of PA-specific splenocytes, significantly stimulated the secretion of IL-4, and enhanced the activation of Dendritic cells (DCs) in vitro. The combination of PCP-I and CpG significantly enhanced the level of anti-PA antibodies and neutralizing antibodies, particularly PA-specific IgG2a, and shifted the Th2-bias to a Th1/Th2 balanced response. In addition, PCP-I with or without CpG could significantly improve the survival rate of immunized mice following challenge with the anthrax lethal toxin. These findings suggest that PCP-I may be a promising vaccine adjuvant that warrants further study.